2016
DOI: 10.1200/jco.2016.34.15_suppl.tps3102
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-human phase I trial of NKG2D chimeric antigen receptor-T cells in AML/MDS and multiple myeloma.

Abstract: Background: Canonical CART cell constructs encode a single chain antibody variable fragment, costimulatory domain, and signaling domain of CD3 zeta. This restricts recognition to 1 tumor antigen and a limited set of cancers. This study employs a novel CAR fusing full-length human Natural Killer Group 2D (NKG2D) gene with the human CD3 zeta signaling domain. NKG2D CAR receives costimulation via naturally-expressed DAP10 and activates T cells directly to kill and secrete cytokines upon recognition of MIC-A, MIC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…CAR T-cell DNA was detected from one hour to one week after infusion in most patients. As expected, the investigators observed neither tumor response nor toxicity after anti-NKG2D CAR T-cell therapy [29].…”
Section: Multiple Myeloma (Mm) and Myeloid Malignanciesmentioning
confidence: 79%
“…CAR T-cell DNA was detected from one hour to one week after infusion in most patients. As expected, the investigators observed neither tumor response nor toxicity after anti-NKG2D CAR T-cell therapy [29].…”
Section: Multiple Myeloma (Mm) and Myeloid Malignanciesmentioning
confidence: 79%
“…3,6 Single intravenous administration of low dose autologous CYAD-01 (maximum 3x10 7 flat dose), without prior chemotherapy, has been tested in a completed Phase I study (clinicaltrials.gov identifier 02203825) which evaluated 12 patients with relapsed/refractory AML (r/r AML), myelodysplastic syndrome (MDS), or multiple myeloma (MM). 11 The preliminary data obtained suggested encouraging signs of activity with one AML patient treated at the 3x10 7 CYAD-01 dose-level having hematologic improvement for three months post-CYAD-01 treatment. 11 Building on these initial results and preclinical data supporting multiple haematologica 2018; 103:e424 CASE REPORTS Figure 1.…”
mentioning
confidence: 83%
“…11 The preliminary data obtained suggested encouraging signs of activity with one AML patient treated at the 3x10 7 CYAD-01 dose-level having hematologic improvement for three months post-CYAD-01 treatment. 11 Building on these initial results and preclinical data supporting multiple haematologica 2018; 103:e424 CASE REPORTS Figure 1. Relapsed AML patient treated with CYAD-01 CAR-T therapy.…”
mentioning
confidence: 83%
“…Single dosing, however, resulted in no clinical leukemic responses future science group www.futuremedicine.com up to 28 days after infusion. Future studies investigating the efficacy of multiple CART-NKG2D infusions are planned [21].…”
Section: Nkg2d Cartmentioning
confidence: 99%